The Moina Gender Investigation using In-Line Digital Holographic Microscopy - Voochaiyaphum, Bunyarit; Thongsuwan, Setthanun; Ruttanasirawit, Chinnapat; Plaipichit, Suwan; Thonglim, Pachara; Buranasiri, Prathan (My University, 2023)
The investigation of Moina was performed using in-line DHM. The reconstructed images of Moinas have been applied for investigation their surface area. Then the surface area has been used for gender investigation.